E-Leadership of Islamic School (Madrasah) Principals in the Implementation of Managerial Competencies - Eci Sriwahyuni; Ainun Mardiyah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: E-Leadership of Islamic School (Madrasah) Principal in Implementing Managerial CompetenciesObjective: This study aims to understand the e-leadership of madrasah principals in implementing managerial competencies. Methods: This research uses a qualitative approach with a case study design. Research informants were selected using a snowball sampling technique, namely the Principal of MTsN Padang Panjang. Data collection used observation, interviews, and document studies. The Miles and Huberman model, used for data analysis, includes data reduction, data presentation, and conclusion drawing/verification. Results: E-leadership of the head of MTsN Padang Panjang plays an important role in implementing managerial competencies in the fields of (1) management of teaching and education personnel, (2) management of students, and (3) management of curriculum and learning. Conclusion: E-Leadership is an effective approach to improving the managerial competence of madrasah heads, strengthening digital-based management innovation, and supporting the transformation of Islamic education in the digital era. Contribution: This research offers a comprehensive and measurable e-leadership model, including innovations in communication, learning, and supervision, which can be a model for madrasah-based educational institutions in improving institutional quality.INDONESIAN: E-leadership Kepala Madrasah dalam Mengimplementasikan Kompetensi ManajerialTujuan: Penelitian ini bertujuan untuk memahami e-leadership kepala madrasah dalam mengimplementasikan kompetensi manajerial. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Informan penelitian dipilih menggunakan teknik snowball sampling yaitu Kepala Sekolah MTsN Padang Panjang. Pengumpulan data menggunakan observasi, wawancara, dan studi dokumen. Model Miles dan Huberman, digunakan untuk analisis data meliputi: reduksi data, penyajian data, dan penarikan kesimpulan/verifikasi. Hasil: E-leadership kepala MTsN Padang Panjang memainkan peran penting dalam mengimpelementasikan kompetensi manajerial baik itu di bidang (1) pengelolaan tenaga pendidik dan kependidikan; (2) pengelolaan peserta didik; (3) pengelolaan kurikulum dan pembelajaran. Kesimpulan: E-Leadership merupakan pendekatan yang efektif untuk meningkatkan kompetensi manajerial kepala madrasah, memperkuat inovasi manajemen berbasis digital, dan mendukung transformasi pendidikan Islam di era digital. Kontribusi: Penelitian ini menawarkan model e-leadership yang menyeluruh dan terukur, mencakup inovasi dalam komunikasi, pembelajaran, dan pengawasan, yang dapat menjadi model bagi lembaga pendidikan berbasis madrasah dalam meningkatkan mutu lembaga.